Enhancing Writing through Digital Storytelling: Storybird - Md Yunus, Melor; Illina Wan Ishak, Wan (International Journal of Engineering and Technology, 2018)
English in the 21st century can be uniquely challenging especially to students due to the fact it is a difficult language to master. One major problem which most students are likely to encounter is ‘writing blocks’ which hinders them from producing good ideas which may lead to their poor writing skills. As a result, students think that writing is a boring activity to do thus feel less motivated to write. However, the wave of 4th industrial revolution has given insight to language teachers to cope with the problem by bringing technology into the classroom in tackling this educational issue. The idea of assimilating digital storytelling inside the classroom is seen as an excellent move in coping with poor writing skills among students. Therefore, this research deals with the use of ‘Storybird’, an artful storytelling platform in enhancing students’ writing skills which was conducted among 40 participants from a semi-rural primary school in Kedah. Classroom observation and task-based learning have been administered in order to collect the data. This research approach also designed to develop and improve teaching and learning in class.  The analysis of the data reveals that most pupils find interactive online writing as stimulating activities in enhancing their writing skills. The findings of the study are hoped to provide teachers and policymakers suggestions in designing interactive lessons which will improve students’ writing skills in a digitally creative manner.